The C-terminal region of alpha-crystallin: involvement in protection against heat-induced denaturation. - Takemoto, L (1993)
Recent studies have demonstrated that the alpha-crystallins can protect other proteins against heat-induced denaturation and aggregation. To determine the possible involvement of the C-terminal region in this activity, the alpha-crystallins were subjected to limited tryptic digestion, and the amount of cleavage from the N-terminal and C-terminal regions of the alpha-A and alpha-B crystallin chains was assessed using antisera specific for these regions. Limited tryptic digestion resulted in cleavage only from the C-terminal region of alpha-A crystallin. This trypsin-treated alpha-A crystallin preparation showed a decreased ability to protect proteins from heat-induced aggregation using an in vitro assay. Together, these results demonstrate that the C-terminal region of alpha-A crystallin is important for its ability to protect against heat-induced aggregation, which is consistent with the hypothesis that post-translational changes that are known to occur at the C-terminal region may have significant effects on the ability of alpha-A crystallin to protect against protein denaturation in vivo.